Number of Kawasaki Disease Admissions Is Associated with Number of Domestic COVID-19 and Severe Enterovirus Case Numbers in Taiwan - Mindy Ming-Huey Guo; Kuender D. Yang; Shih-Feng Liu; Ho-Chang Kuo (MDPI AG, 2022)
Background: Non-pharmaceutical interventions (NPIs) introduced in response to the COVID-19 pandemic, including mask-wearing and social distancing, have changed the prevalence of circulating viruses in the community. Since viral infections represent a potential triggering factor for the development of Kawasaki disease (KD), we examined the relationship between KD admission rates and the number of COVID-19, severe influenza, and severe enterovirus infections both before and after the COVID-19 pandemic. Methods: We conducted a retrospective study using data obtained from the Chang Gung Research Database (including seven Taiwanese hospitals and more than 10,000 beds) and the Centers for Disease Control in Taiwan from January 2018 to December 2020. We recorded the number of KD admissions, as well as COVID-19, severe influenza, and severe enterovirus infections. Results: The numbers of KD admissions, severe enterovirus infections, and severe influenza infections were significantly lower from April to September 2020. The number of KD hospitalizations was positively correlated with the number of domestic COVID-19 cases (p = 0.001). A decrease in KD admission numbers was positively correlated with a decrease in severe enterovirus case numbers (p = 0.007). Conclusion: Our findings provide further evidence that viral infections may be an important trigger factor in the development of KD. Therefore, NPIs may not only prevent transmissible viral infections in children, but also decrease the risk of KD.